Evaluación de tipologías de sistemas agroforestales en fincas de café en las sub cuencas de Yuracyca y Yanayacu - Montalván Ruiz, Jorge Darwin (2015)
farms in the sub-basins of Yuracyacu and Yanayacu, 2014, has the purpose of georeferencing the demonstration plots in the agroforestry systems of coffee farms from each site in the research, likewise, to determine the line bases for the evaluation of typologies in systems agroforestales of coffee, to determine the typologies in the managing coffee with the best performance, as well as also to identify the environmental impacts. The study was conducted in 1 O farms of coffee producers in the Alto Mayo region - San Martín: 4 farms in the ofMoyobamba province and 6 farms in Rioja province associated in coffee organizations. For identifying the features that the grower performs at their country estate; to get to meet the objectives of this research methodology was used, techniques and materials that allowed us to gather field data. The results ofthis investigation were important for coffee cultivation in the region that is already achieving georeference a total of 1 O si tes of different vegetation covers as well as coffee (42.67 ha), grass (23.79 ha), purma (10.82 ha), forest (27.38 ha), bread carry (0.59 ha), others (0.05 ha). The bread products carry are associated with the cultivation of coffee ( "cassava" - Manihot esculenta, "banana" - Musa paradisiaca), of the 1 O farms assessed only the ranch N° 01 has vegetation cover of bread as a separate area (0.59 ha) "cassava" - Manihot esculenta. The line decided base for the evaluation of typologies in agro forestales systems of coffee, identifying for the type of managing ofthe estate 6 organic producers, conventional2 and traditional2; the variety of coffee that the producers prefer on their farms are Catimor (60 % ), Caturra (38.88 %) and Pache (10% ); ofthe 10 producers only 8 have nursery in their farm. The coffee trees density in 0.5 ha was 1250 plants (2500 coffee trees/ha) farro N°. 10 and 1866 individuals in the ranch N° 05 (3732 coffee treeslha); higher density of shade trees in the coffee plantation was in the ranch N° 05 ( 66 individuals) and in the ranch No 07 was not found shade trees, between the 1 O coffee farms was identified 3 7 species that makes a total of357 trees ofwhich 211 were "guabas"- lnga Edulis (59.10 % ), more representative species and preferred by the vast majority of the producers on their farms, 18 trees were "faceted" - Cecropia membranacea (5.04% ), 16 trees were "screw" - Cedrelinga catenaeformis (4.48% ); in regard to the waste water honey: 8 producers as discarded to wells, 2 producers the disposing of ravines and a producer has disposed on the surface ofthe soil; the waste ofthe coffee pulp: 9 producers the compost and a producer makes it spoil. It was determined that, the typologies in the handling ofthe coffee with the best economic performance of the 1 O farms production according to the type of organic management obtained 6 qq/ha, the coffee farm with the conventional management obtained a harvest of 11 qq/ha and the traditional finca won 4 qq/ha. With regard to environmental impacts; the higher practice of soil conservation by the manufacturers is to keep the litter, the impact on the ecosystem in the farms is that these are the wildlife refuge. All the activities of the coffee production process generate environmental impacts on the ecosystem from the germinator until the profit system. According to the Ecological Economic Zoning (ZEE), the estate N o O 1 is located in a zone of municipal conservation, the estates N o 02, 06 and 09 in zones of recovery of forest lands associated with lands for permanent culture, the estates N° 03 and 04 are areas of protection of bedside of watershed, the estates N° 05 and 1 O are found in areas of protection and permanent crops of agricultura} quality low with limitations due to slope and soil, the estates N° 07 and 08 are located in the buffer zone ofthe Alto Mayo Protection Forest. Finally, this research helps to identify the handling characteristics of coffee in agroforestry systems as well as to identify what are the environmental impacts generated by the activities in the productive process. Key words: agroforestry systems, environmental impacts.